Exploring the influence of service quality (SQ) on patient satisfaction (PS): A case study of Universiti Malaysia Pahang Health Centre (UMPHC) - Abdul Basit, Khairul Salleh; Hussain, Suhaidah (Penerbit Universiti Malaysia Pahang, 2022)
Patient satisfaction and healthcare service quality has been studied for ages. Primary care centre such as UMP Health Centre (UMPHC) is the intermediaries between patients and hospital referral. Hence, they have the most contact and influence on customers because they are convenient and strategic, and become the primary direct contact with patients on a daily basis, especially the university community. As healthcare organizations are trying to improve their return on investment, UMPHC has started to implement steps in curbing patient dissatisfaction issues with the study of service quality and patient satisfaction. In this paper, the author looks into the dimensions of service quality that influence patient satisfaction in their visits and appointments at UMPHC. The impact of various service quality dimensions on patient satisfaction is studied to understand how those factors relate to the patient’s expectations and perceptions. In this qualitative case study, semi-structured interviews were conducted with fourteen students and four staff who visited UMPHC and the results were analyzed through thematic analysis. In this research, seven themes namely responsiveness, reliability, assurance, empathy, tangible, technical quality, and elements that could improve patient satisfaction are created which further branches to a total of 21 sub-themes. The location of UMPHC or accessibility to the services, dental services, staff’s attitude and communication skills, consistency in following the standard operating procedures, waiting time, technical quality as well as health education were amongst the most important factors affecting patient satisfaction. The UMPHC health managers are recommended to focus on the above aspects and implement appropriate management decisions to improve patient satisfaction.